2019
DOI: 10.1111/jam.14508
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐borne endophytic Bacillus velezensis LHSB1 mediate the biocontrol of peanut stem rot caused by Sclerotium rolfsii

Abstract: Aims This study aimed to obtain an antagonistic endophyte against Sclerotium rolfsii from peanut seeds, evaluate the biocontrol efficacy towards peanut stem rot and explore its antifungal mechanism against S. rolfsii. Methods and Results Thirty‐seven endophytic bacteria were isolated from peanut seeds, six of which exhibited stronger antagonistic activities against S. rolfsii (inhibition rate, IR of hyphae growth ≥70%). Strain LHSB1, the strongest antagonistic strain, was identified as Bacillus velezensis. LHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 38 publications
1
26
0
3
Order By: Relevance
“…Antagonistic activity against the pathogens Monilinia fructicola [ 61 ] and B. cinerea (60%) reached maximum levels of > 80% and 60%, respectively, mainly due to the large amount of lipopeptides produced (10 g/L) [ 67 ]. Many studies of olive, tomato, corn, peanut, pepper, maize and rice crop yields have also described the biocontrol activity of B. velezensis strains against phytopathogens such as Verticillium dahliae , Fusarium graminerarum , Sclerotium rolfsii , Phytophthora and B. cinerea [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Our results are in line with the findings of Lee et al (2006) [ 75 ] who investigated the effect of radicular applications of B. subtilis WXCDD105 on B. cinerea in tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic activity against the pathogens Monilinia fructicola [ 61 ] and B. cinerea (60%) reached maximum levels of > 80% and 60%, respectively, mainly due to the large amount of lipopeptides produced (10 g/L) [ 67 ]. Many studies of olive, tomato, corn, peanut, pepper, maize and rice crop yields have also described the biocontrol activity of B. velezensis strains against phytopathogens such as Verticillium dahliae , Fusarium graminerarum , Sclerotium rolfsii , Phytophthora and B. cinerea [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Our results are in line with the findings of Lee et al (2006) [ 75 ] who investigated the effect of radicular applications of B. subtilis WXCDD105 on B. cinerea in tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Many PGP endophytic microbes are widely accepted as biofertilizers, biostimulants, and biocontrol agents [ 11 , 13 , 49 ]. These microbes exert antagonistic effects by producing antibiotic compounds, lipopeptides, cell wall degrading enzymes, volatile compounds, hydrogen cyanide (HCN), and siderophores [ 50 , 51 , 52 , 53 ]. Some of these beneficial microbes aggregate the soil particles to improve the soil structure and secrete extracellular metabolites to augment the breakdown of complex organic material and insoluble nutrients into simple, more available forms [ 54 ].…”
Section: Plant Microbiomes: the Origin Of Plant Probiotic Bacteriamentioning
confidence: 99%
“…Abo-Zaid et al [34] used a talc-based medium to ferment Streptomyces cellulosae Actino 48 with a high chitinase production which could effectively inhibit the mycelial growth of Sclerotium rolfsii. The rhizosphere growth-promoting bacteria Bacillus pumilus LX11 [14] and the seed endophytes Bacillus velezensis LHSB1 [35] can effectively antagonize Sclerotium rolfsii to signi cantly reduce the incidence of stem rot and can be used as potential biocontrol agents. The present research found that the high concentration fermentation solution of Novosphingobium panipatense, a dominant strain signi cantly enriched by calcium at the pod lling stage, could signi cantly inhibit the mycelial growth and nucleus formation of Sclerotium rolfsii.…”
Section: Discussionmentioning
confidence: 99%